Cultural Psychology, Social Identity, and Community Engagement in World Heritage Conservation Sites - ROSILAWATI, Y.; RAFIQUE, Z.; HABIB, S.; NURMANDI, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research uses the case study of world heritage sites from South Asia and the Asian Pacific region. It aims to explore how macro cultural psychology, social identity, and community engagement influence the conservation of world heritage sites. The data for this paper was collected from three Asian countries namely Indonesia, Pakistan, and Malaysia. FGDs and In-depth interviews from all the stakeholders were conducted, also, data analysis were made. The paper found that in all three countries heritage site remnants are used to create social identity, making macro psychology and engaging communities.RESUMEN Esta investigación utiliza el estudio de caso de sitios patrimonio mundial del Sur de Asia y de la región del Asia Pacifico. Tiene como objetivo explorar cómo la psicología macrocultural, la identidad social y el compromiso de la comunidad influyen en la conservación de los sitios patrimonio mundial. Los datos para este documento se obtuvieron de tres países asiáticos, a saber, Indonesia, Pakistán y Malasia. Se realizaron grupos focales y entrevistas en profundidad a todos los interesados, ademas, se llevó a cabo un análisis temático de datos. El documento encontró que en estos tres países las ruinas de sitios patrimoniales, se utilizan para crear identidad social, macro psicología e involucrar a las comunidades.